HRD policy implementation in Malaysian public universities - an investigation of the relationship between organisational factors and implementation. - Baharom, A. (2008)
There have been major developments in the way organisations are dealing with the changing patterns and increased speed of the workplace. Organisations public and private have to currently wrestle with the need to improve their human capital and to answer the requirements for a highly skilled workforce to address the challenges they are facing in a more dynamic and globalise work environment. The workplace has now been re-orientated to be one of the best and most effective venues for learning. This discovery has prompted the Malaysian government to put added emphasis on developing first class mentality in the human capital in the country. These requirements and the cry for improvements in implementation activities in the public sector have compelled the government to improve competencies of public personnel and service delivery within their workforce. The concern of the population is for a transformation in the implementation system that is currently perceived to be bureaucratic and slow to change with the times. The government’s seriousness in addressing these issues is visible when the Prime Minister set up a body with the sole responsibility of looking into ways to improve implementation and service delivery in the nation. Public policies, procedures, guidelines are the public sector’s mantra towards efficiency. However, without sound implementation, policies and programs will be an utter waste of time and resources. It is on this note that this study has taken place. The objective of this study is to investigate organisational factors influencing policy implementation with special focus on HRD policy within the Malaysian public universities. Factors included in this study are departmental communications, characteristics of implementing departments and dispositions of implementers. This study will also highlight findings pertaining to the relationships between organisational factors and implementation in public universities.